Temple Encyclopedia Application Based on Android (East Java Temple Case Study) - Sasmito Bagus Sumadyo; Suprianto (Procedia of Engineering and Life Science, 2021)
The purpose from this research is to designing and to produces a mobile application of Encyclopedia which can give data information of related temple that they just visit. Research’s method is using waterfall method, the technique to collecting data using seconder data technique which temple’s data have been collected from book printed by Ministry of Education and Culture. Product from this research is temple’s visitor can get information about temple related with mobile by scanning qrcode.